2020
DOI: 10.21037/tcr-20-1028
|View full text |Cite
|
Sign up to set email alerts
|

Possible local treatment for liver metastases of adenoid cystic carcinoma (ACC): single-centre experience and literature review

Abstract: Background: Adenoid cystic carcinoma (ACC) is a relatively indolent cancer, for which the major cause of death is distant metastases. The median survival time of patients with distant metastases of ACC is approximately 20 months. Although the liver is not the most common site of secondary ACC, effective treatment of liver metastases could improve patient survival. This study explored the clinical features and treatment of liver metastases of ACC in one centre and performed a literature review. Methods: This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Prior studies have reported liver metastasis of solid-type ACC, but no case described a clinical course similar to the one seen in this patient, with initial misdiagnosis as nasopharyngeal carcinoma. [6][7][8][9] The patient initially received six days of radiation therapy, which seemed to mitigate her pain with no changes in her vision loss. Despite this improvement, her course again became complicated with unusual findings on a CT of the chest/abdomen/ pelvis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported liver metastasis of solid-type ACC, but no case described a clinical course similar to the one seen in this patient, with initial misdiagnosis as nasopharyngeal carcinoma. [6][7][8][9] The patient initially received six days of radiation therapy, which seemed to mitigate her pain with no changes in her vision loss. Despite this improvement, her course again became complicated with unusual findings on a CT of the chest/abdomen/ pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A retrospective review found ACC with liver metastasis originating from the nasopharynx, but it did not include any clinical descriptions of the cases. 7 In our case study, we describe an uncommon presentation of a patient who developed adenoid cystic carcinoma of the nasopharyngeal salivary glands that ultimately metastasized to the liver.…”
Section: Introductionmentioning
confidence: 96%